Penyesuaian Diri pada Menantu Perempuan yang Tinggal di Rumah Mertua - Dinar Hardi Mantrayani; Ellyana Ilsan Eka Putri (INCARE, International Journal of Educational Resources, 2024)
Marriage is a bond between two individuals who dicide to live together. Many couples begin their married life by living with their parents, resulting in more complex dynamics and adjustment processes. This research employs a qualitative phenomenological method with three participants. Data collection techniques include interviews. Data validity is tasted through member checks and expert judgment. The result of this study indicate that participants are able to adjust to living with their in-laws, with supporting factors including physical condotions, development and maturity, psychological state, as well as cultural and religious conditions. Conflicts encountered by daughters-in-law living with their in-laws include misunderstandings about household cleanliness, differences in daily activities, and child-rearing practices.